2016
DOI: 10.1200/jco.2015.62.2985
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictive Factors for Recovery of Ovarian Function in Amenorrheic Women in Their 40s Treated With Letrozole

Abstract: These results emphasize the challenge in determining definitive menopause in women with chemotherapy-induced amenorrhea. The risk of OFR during treatment with AIs in amenorrheic women in their 40s is high, and AI therapy should be avoided in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
11
0
5
Order By: Relevance
“…Prediction of POI is well established to be dependent on age [6] , [7] , [13] but the value of biochemical markers has been unclear [28] . Thus, in a recent analysis, women showing ovarian recovery did not show differential FSH concentrations [29] . We have previously suggested that high-sensitivity AMH assays may be of value in this situation [22] .…”
Section: Discussionmentioning
confidence: 81%
“…Prediction of POI is well established to be dependent on age [6] , [7] , [13] but the value of biochemical markers has been unclear [28] . Thus, in a recent analysis, women showing ovarian recovery did not show differential FSH concentrations [29] . We have previously suggested that high-sensitivity AMH assays may be of value in this situation [22] .…”
Section: Discussionmentioning
confidence: 81%
“…V recentně publikované práci bylo pozorováno obnovení ovariální funkce v souboru 177 nemocných u 39 % z nich. Sérová hladina FSH s obnovením ovariální funkce nekorelovala, jejím signifikantním prediktorem byl pouze věk < 45 let a inhibin B [26]. Podobně v prospektivní studii, ve které byly pa cientky s CIA po nejméně dvou letech podání tamoxifenu léčeny exemestanem za monitorace hormonálních hladin, byla incidence obnovení ovariální funkce 32 %, medián doby do OFR byl 5,4 měsíce (95% CI 1,2-9,6) a jediným signifikantním prediktorem byl průměrný věk při zahájení léčby exemestanem < 48 let.…”
Section: Vazomotorické Příznakyunclassified
“…U žen s nejasným menopauzálním stavem je bezpečnou léčbou tamoxifen. Indukce zbytkové ovariální funkce (ovarian function recovery -OFR) inhibitorem aromatázy byla opakovaně popsána různými autory [18,26,27]. Chemoterapií indukovaná amenorea (chemotherapy--induced amenorrhea -CIA) nemusí být 3S43 čiva.…”
Section: Rizika Při Léčbě Pa Cientek Mladších 50 Letunclassified
“…Other markers, including FSH, anti-Mullerian hormone (AMH), and inhibin, may provide additional information on ovarian status in female cancer survivors with prior chemotherapy or those on tamoxifen, but alone are not reliable to ensure menopausal status. 19,20 …”
Section: Menopausementioning
confidence: 99%